Awareness towards fertigation system at Polytechnic Jeli Kelantan (PJK) / Suza Hamira Suhaimin - Suhaimin, Suza Hamira (2011)
This study investigated the awareness towards fertigation system among 102 respondents from Polytechnic Jeli Kelantan (PJK). There are 39 female and 63 male. Three variables involved in this study are understanding, perception and attitude for this study. This study is cross-sectional design. Cluster sampling method was used in this study and the questionnaire was distributed with self-administrative. The study was analyzed using SPSS 18.0 for descriptive analysis while Amos 18.0 was used for Structural Equation Modeling (SEM). The result shows that all of test on demographic variable (age, gender, level qualification and types of category occupation) is no significant influence to the respondent’s awareness. It explains that, that the respondents come from difference gender, age level qualification and types of category occupation they will have same awareness towards fertigation system. On the main hypothesis testing the results showed that perception and understanding has significant influence on awareness towards fertigation system. Recommendation on this study, PJK should do the program workshop on fertigation system for students and staffs. With this program, it may be able to open the minds of students and staff about the benefits of fertigation system and also can provide an attractive income to staff and student